2013
DOI: 10.1142/s179398441330001x
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry and Biology of Gold Nanoparticle-Mediated Photothermal Therapy: Promises and Challenges

Abstract: Under laser radiation, cells labeled with gold nanoparticles (AuNPs) are believed to suffer thermal damage due to the transfer of the absorbed light from the AuNPs to the cells. This process, which involves complex mechanisms such as the rapid electron–phonon decay in the AuNPs , followed by phonon–phonon relaxation, culminates in the localized heating of both the AuNPs and the cells, setting the rational for the use of these nanostructures, under laser light, in cancer photothermal therapy (PTT). Here, we dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 127 publications
0
39
0
Order By: Relevance
“…The AuNPs’ photoexcitation at their SPR maximum wavelength results in an efficient light-to-heat conversion [18,26]. Depending on the amount of heat generated and transferred to the surroundings, it can compromise or destroy cells, whether the AuNPs are within cancer cells or on their surface [39]. In addition, tumor tissue is thought to be more hypoxic, acidic, and nutrient-deficient than normal tissues, traits that are believed to increase the sensitivity of cancer cells to heat, though the effects of thermal therapy are dependent on cancer type [40].…”
Section: Addressing Current Drawbacks In Gene Silencing Therapy—fomentioning
confidence: 99%
See 2 more Smart Citations
“…The AuNPs’ photoexcitation at their SPR maximum wavelength results in an efficient light-to-heat conversion [18,26]. Depending on the amount of heat generated and transferred to the surroundings, it can compromise or destroy cells, whether the AuNPs are within cancer cells or on their surface [39]. In addition, tumor tissue is thought to be more hypoxic, acidic, and nutrient-deficient than normal tissues, traits that are believed to increase the sensitivity of cancer cells to heat, though the effects of thermal therapy are dependent on cancer type [40].…”
Section: Addressing Current Drawbacks In Gene Silencing Therapy—fomentioning
confidence: 99%
“…Nowadays, in order to localize and moderate the heat, diverse heating sources are used, for instance, radiofrequency microwaves and ultrasounds. More recently, medical procedures have been revolutionized with the discovery of lasers, which allow an even more precise thermal damage to tumor tissue [39]. Metal nanoparticles, especially AuNPs, have shown unique photophysical properties.…”
Section: Combinatory Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the possible imaging modalities using AuNPs, we may include light scattering imaging, surface-enhanced Raman spectroscopy, photoacoustic imaging, x-ray computed tomography, two-photon fluorescence imaging and MRI [13].…”
Section: Gold Nanoparticles As Platforms For Nanotheranosticsmentioning
confidence: 99%
“…Because the silencing moiety is bonded to the AuNPs, the antisense oligonucleotide shows an increased halflife in the presence of nucleases, since it has been shown that AuNPs confer considerable protection against enzymatic degradation [16,17]. What is more, the PEGylated AuNPs are extremely stable under physio logical conditions and will be able to evade macrophage clearance, thus increasing their in vivo efficacy [6,13]. Perhaps one of the most relevant features of such a design is the capability conveyed by the AuNPs to act as efficient transfection agents in aqueous media (i.e., the AuNPs act as carriers or vectors for the silencing moiety and confer protection while being an active part of the imaging and tracking of the events).…”
Section: Gold Nanobeacons As Nanotheranostics Platformsmentioning
confidence: 99%